2017
DOI: 10.7150/jca.18893
|View full text |Cite
|
Sign up to set email alerts
|

HOXC6 Overexpression Is Associated With Ki-67 Expression and Poor Survival in NPC Patients

Abstract: BACKGROUND: Homeobox (HOX) genes are expressed in adult cells and regulate expression of genes involved in cell proliferation as well as cell-cell and cell-extracellular matrix interactions. Dysregulation of HOX gene expression plays important roles in carcinogenesis in a variety of organs. Through data mining on a published transcriptome dataset, this study first identified Homeobox protein Hox-C6 (HOXC6) gene as one of the differentially upregulated genes in nasopharyngeal carcinoma (NPC). We aimed to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…A previous study highlighted overexpression f HOXC6 in tumor tissues of colorectal cancer [26]. It has been reported that there are correlations of HOXC6 overexpression with increment of tumor stage, advanced nodal status in nasopharyngeal carcinoma [27].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study highlighted overexpression f HOXC6 in tumor tissues of colorectal cancer [26]. It has been reported that there are correlations of HOXC6 overexpression with increment of tumor stage, advanced nodal status in nasopharyngeal carcinoma [27].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that HOXC6, as a member of the HOX gene family, was overexpressed in various cancers, and played a key role in promoting cancer progression, suggesting that HOXC6 was a potential biomarker for diagnostic, prognostic and therapeutic target of cancers 1618. For instance, Chen et al found that HOXC6 gene significantly promoted the proliferation, invasion and metastasis of gastric cancer cells by upregulation of MMP9, which was associated with the poor prognosis of gastric cancer patients 19.…”
Section: Introductionmentioning
confidence: 99%
“…The pooled data were as follows: HR = 2.86, 95% CI = 1.91–4.27, p < 0.001, indicating that high Ki-67 expression predicted poor OS. Similarly, the combined HRs and 95% CIs from six studies, 16 19 , 22 , 23 and three studies, 18 , 19 , 23 showed that Ki-67 overexpression was also correlated with worse PFS (HR = 1.78, 95% CI = 1.15–2.74, p = 0.009; I 2 = 52%, p = 0.064) and unfavorable DMFS (HR = 1.65, 95% CI = 1.15–2.36, p = 0.007; I 2 = 23.4%, p = 0.271) ( Figure 2 , Table 2 ). However, no significant correlation was found between high Ki-67 expression and LRFS (HR = 1.07, 95% CI = 0.54–2.14, p = 0.843; I 2 = 52.1%, p = 0.124) based on the data of three studies.…”
Section: Resultsmentioning
confidence: 99%